Prevalence of and factors associated with tuberculosis medication adherence among pulmonary tuberculosis patients registered in the DOTS program in Banke district, Nepal - KC, Sumit; Bhattarai, Srijana; Khatiwada, Kabita; Shah, Shalabh; Sapkota, Samjhana (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Tuberculosis (TB) remains a major public health challenge worldwide. Non-adherence to treatment among TB patients threatens control efforts. This study aimed to assess the prevalence of and identify factors associated with medication adherence for pulmonary tuberculosis (PTB) among patients registered under the Directly Observed Treatment Program (DOTS) in Banke District, Lumbini Province, Nepal. Method: A community-based cross-sectional study was conducted among 385 patients with PTB, using stratified and random sampling, and data were collected via telephone interviews. Descriptive and inferential analyses were used. Logistic regression was performed, and p-values less than 0.25 in the bivariate analysis were considered for inclusion in the multivariate logistic regression analysis. Data analysis was done using STATA v13. Result: The prevalence of PTB adherence was 95.58% (95% CI 92.9%-97.2%). Factors significantly associated with adherence included knowledge about TB, walking distance to DOTS centers, waiting time at DOTS centers, and whether health education was provided. Patients with poor knowledge, longer travel or wait times, and those who did not receive health education were significantly less likely to adhere to treatment. Conclusion: However, the prevalence of PTB adherence was 95.58%. Interventions to improve knowledge, reduce access barriers, and provide health education are recommended to achieve 100% adherence. Programs aimed to emphasize the establishment and expansion of community-based DOTS programs and address existing barriers to 100% adherence to the treatment.